Determinants of driving factors in practicing energy efficiency in Malaysian public Uuiversity buildings / Muhammad Hafizzudin Mohamad Nasir ... [et al.] - Mohamad Nasir, Muhammad Hafizzudin; Lop, Nor Suzila; Mohd Kamar, Izatul Farrita; Mat Salleh, Norazlin (2021)
Energy is the main element in building operations. It is crucial to ensure that the operation and services in that building can be carried out effectively. Naturally, energy is produced from fossil fuels. In Malaysia, the overall energy demand rises at an average annual rate of 6.3 per cent due to the expected higher growth in Growth Domestic Product (GDP). However, high energy consumption will cause the buildings to release more Carbon Dioxide (CO2) which results in greenhouse gas (GHG) emissions. Therefore, it is vital for all buildings to practice energy efficiency (EE) to ensure that the buildings consume minimum energy and produce maximum output during operation. Thus, this research aimed to determine the driving factors that facilitate the implementation of EE in public university buildings. A quantitative approach via a questionnaire survey was adopted. A purposive sampling technique was used which listed 69 respondents who were directly involved in building maintenance and energy efficiency as respondents. The data were analysed using the Statistical Package for Social Science (SPSS) version 25 quantitative software. The results reveal that seven factors were identified as barriers in the implementation of EE in public university buildings. In relation to that, ten driving factors to facilitate the implementation of EE in Public University buildings were found to overcome barriers in the practice of EE of a building. The findings of this research might benefit practitioners in promoting EE practices to achieve cost reduction through low energy usage.